UPAYA PENANGGULANGAN KEMISKINAN BERBASIS PEMBERDAYAAN MASYARAKAT LOKAL (Belajar dari Pelaksanaan Program Penanggulangan Kemiskinan Perkotaan di Kelurahan Bintoro, Kecamatan Demak, Kabupaten Demak - TAUFIQ DKK, TAUFIQ DKK (Politika: Jurnal Ilmu Politik, 2010)
AbstractGovernment makes policy to solve problems affecting people in society. Making policy meansdeciding what is and is not a problem, choosing which problem to solve, and deciding how to solvethem to benefit society. P2KP(Urban Poverty Project) program, one of those programs to solve thepoverty problem in urban area. P2KP program implelemented poverty alleviation in urban area basedon three pillars of empowerment. Firstly, physical empowerment; secondly, economic empowerment;thirdly, social empowerment. The study found that P2KP program are successfully implemented inphysical and social empowerment. It is necessarily have to investigate further research to answer thatthe program unsuccessfully implemented in economic empowerment.Key-word: Poverty alleviation, urban area, economic and social empowermentA. PENDAHULUAN